Panic and Anxiety Disorder: Multifactorial Conditions (Research, Society and Development, 2022)
This study aimed to research Panic and Anxiety Disorder, considering the multifactorial conditions, as well as the treatments, since panic is a nosological entity accompanied by important psychic and functional impairment. PD It is characterized by repeated attacks of intense anxiety without specific circumstances, being unpredictable. Its symptoms vary from person to person, but palpitations and chest pain, feelings of unreality and fainting, fear of losing control or dying are common. Currently, the diagnosis of PD must comply with a series of criteria listed in international classifications, such as the International Classification of Diseases and Related Health Problems (ICD 10) and the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV). The development of this work was carried out through a bibliographic review, a qualitative approach and the methodology used is explanatory research. Panic is a chronic disorder with low rates of long-term symptom remission. Therefore, it is suggested that new studies be designed for the early treatment of anxiety disorders.